SAFETY OF SINGLE LAYER CONTINUOUS EXTRA MUCOSAL GUT ANASTOMOSIS IN EMERGENCY - Ahmed, Munir; Amer, Saeed; Alam, Shahid; Ullah, Asad; Sadiq, Muzafar Uddin; Khan, Muhammad Amjad (Journal of Postgraduate Medical Institute, 2012)
Objective: To evaluate the safety and complications of a single layer continuous extra mucosal gutanastomosis in emergency. Methodology: This descriptive study was conducted in emergency department of Lady Reading HospitalPeshawar over a period of ten months from September 2007 to July 2008. Study comprised of fiftyconsecutive patients after fulfilling the inclusion and exclusion criteria. The safety of anastomosistechnique was analysed by postoperative complications of morbidity and mortility. Result: Among 50 patients 80 % were male and 20 % were female, mainly young adults. Patients withanastomotic leakage were 8%. The rate of wound infection was 34 %. Mean hospital stay was 7.22 days.Mortality was 8% due to septicemia and hypovolumic shock. Conclusion: Single layer continuous extramucosal anastomosis is safe and with less anastomosis-relatedmorbidity and mortality.